A case-control study of mesothelioma in South Africa - Rees, David John (Department of Public Health and Family Medicine, 2017)
This thesis reports the results of a prospective multicentred case-control study of mesothelioma carried out in South Africa. The objectives of the study were: 1) to examine asbestos exposure of cases in detail with respect to source, risk occupations, fibre type and duration; 2) to determine relative risks for level (certainty) of exposure (definite, probable, possible, unlikely), for category of exposure (occupational, environmental), and for fibre type and skin colour; 3) to determine whether cases without recall of exposure were exposed to other non-asbestos putative agents; 4) to investigate the possible protective effect of certain dietary components. Previous studies of mesothelioma in South Africa had, with the exception of one incidence study, focused on particular occupational or case material, exposure data had been gathered in a non-systematic way, often indirectly from surrogates, and non-asbestos agents had not been investigated. In this case-control study these issues are all addressed. In addition, special efforts were made to minimise potential sources of bias (e.g. interviewer bias) and so to furnish reliable effect estimates. The study incorporated the following methodological features: 1) a prospective approach to gather exposure and dietary information directly from the cases and controls in life and so avoid the use of surrogates for this information; 2) the study was multicentred with study teams established in six cities, each with a major referral hospital, to maximise nation-wide coverage; 3) information was gathered with interviewers blind (at least at the beginning of the study) to study objectives and case control status at the time of the interview; 4) rigorous pathologic review was used to establish the diagnosis of mesothelioma; 5) two controls were selected for each case, a cancer and a non-cancer patient matched for hospital, sex, age and skin colour; 6) in analysis the case control datasets were treated separately (i.e cases and cancer controls, and cases and non-cancer controls were treated as two separate datasets). One hundred and twenty three cases were accepted into the study. No case was documented with purely chrysotile exposure nor exposure to a putative non-asbestos cause of the tumour without some evidence of asbestos exposure. A minimum of 22 cases (18%) had exclusively environmental exposure, 20 were from the NW Cape (a crocidolite mining region). Fifty eight percent had occupational exposure, three of whom had mined amosite. The relative risks associated environmental exposure in the NW Cape were larger than for environmental exposure in the NE Transvaal: 21.9 versus 7.1 for the cancer control dataset and 50.9 versus 12.0 for the medical control dataset. Increasing consumption of carotene rich fruit was found to be protective for mesothelioma when adjusted for asbestos exposure. The results confirm the high disease burden due to occupational exposure, the importance of environmental exposure in the crocidolite mining area of the NW Cape, the relative paucity of cases linked to amosite, the rarity of chrysotile cases, and are consistent with the view that there is a fibre gradient in mesotheliomagenic potential for South African asbestos with crocidolite > amosite > chrysotile. The evidence for a protective effect of carotene rich fruit is new in the South African context.